Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1093/emboj/17.8.2148
|View full text |Cite
|
Sign up to set email alerts
|

Dileucine-based sorting signals bind to the beta chain of AP-1 at a site distinct and regulated differently from the tyrosine-based motif-binding site

Abstract: In previous work, we showed that peptides from endocytosed proteins containing the tyrosine YXXphi sorting motif are recognized by the mu 2 subunit of AP-2, the plasma membrane clathrin adaptor protein complex. This interaction is activated by phosphoinositide lipids that are phosphorylated at the D-3 position of the inositol ring, and is also enhanced by the formation of clathrin-AP-2 coats. Here, we describe the detection of a specific interaction between peptides containing a second sorting motif, the dileu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
212
3
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(228 citation statements)
references
References 54 publications
4
212
3
9
Order By: Relevance
“…0.5% Triton X-100). Because the affinity of adaptor complexes for potential cargo molecules was previously shown to be very weak in vitro, some binding may not have been detected in our experiments (18). Yet the fact that no other SNARE-adaptor binding was detected emphasizes the significance of the AP-1-VAMP4 interaction.…”
Section: Discussionmentioning
confidence: 64%
“…0.5% Triton X-100). Because the affinity of adaptor complexes for potential cargo molecules was previously shown to be very weak in vitro, some binding may not have been detected in our experiments (18). Yet the fact that no other SNARE-adaptor binding was detected emphasizes the significance of the AP-1-VAMP4 interaction.…”
Section: Discussionmentioning
confidence: 64%
“…Clathrin-coated pit formation recruits a clathrin lattice and the AP-2 complex to the plasma membrane, whereas AP-1 is lured to the trans-Golgi network. In this process, dileucine motifs interact with the ␤1 subunit of AP-1 (40), directing the sorting of proteins to the trans-Golgi network. The structural determinants and the mechanisms underlying BLT1 endocytosis are still not defined, but we have previously demonstrated that BLT1 C-tail is essential for BLT1 internalization, as it is for a vast number of GPCRs, and that this phenomenon is uniquely independent of arrestins.…”
Section: Discussionmentioning
confidence: 99%
“…However, in only a very few cases have membrane proteins and adaptors co-immunoprecipitated (20). Several in vitro assays, including bead pull-down and surface plasmon resonance, had shown interaction between tyrosine-based sorting signals and clathrin adaptor complexes (21)(22)(23)(24)(25), yet surprisingly few data are available concerning whether such interactions occur in vivo or are physiologically important. Although a direct interaction between YXX⌽ internalization sequences and 2 subunits has been demonstrated, the binding of receptors to AP-2 does not necessarily correlate with the internalization capacity of proteins bearing YXX⌽ motifs.…”
mentioning
confidence: 99%